Conflict Management Strategies of Islamic Boarding Schools in Building Social Relations with Communities: A Study at Al-Istiqomah Tanjungsari Kebumen - Abdi Setiawan; Robingun Suyud El Syam; Rifqi Muntaqo; Muhamad Yusuf Amin Nugroho; Alfiana Agustin (ADARA, 2025)
This study is motivated by the efforts of Al-Istiqomah Islamic Boarding School in Tanjungsari, Petanahan, Kebumen to build and maintain harmonious relationships with the surrounding community amid the dynamics of Islamic education management. In practice, the pesantren faces various conflicts, including issues related to the establishment of the Al-Istiqomah Karya Guna Education Foundation (YAPIKA), the development of facilities and infrastructure, and students’ activities that affect community life. These conditions require effective conflict management to ensure that educational processes continue optimally. This study aims to identify the forms of conflict between the pesantren and the community, analyze the conflict management strategies applied, and examine the outcomes of their implementation at Al-Istiqomah Islamic Boarding School. The research employed a qualitative approach with a field research design. The research subjects included the pesantren leader, foundation administrators, pesantren managers, and members of the surrounding community. Data were collected through interviews, observations, and documentation, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing.The findings indicate that conflicts included communication misunderstandings, issues related to facility development, and students’ activities in the community. Conflict management was carried out through stages of problem identification, conflict analysis, approach determination, strategy implementation, and continuous evaluation. The implementation of conflict management had positive impacts on the smooth development of facilities and infrastructure, strengthened partnerships between the pesantren and the community, adjustments to internal regulations, and improvements in the management of students’ activities. These findings highlight the importance of conflict management in sustaining pesantren-based education grounded in social harmony.